CO2 Absorption in a Microstructured Mesh Reactor - Constantinou, Achilleas; Gavriilidis, Asterios (My University, 2010)
Carbon dioxide absorption in sodium hydroxide solution was studied in a metal mesh microstructured reactor. The reactor comprised of a microstructured metal mesh placed between two acrylic plates. Channels were machined in the plates with 0.85 mm and 0.2 mm depth forming the areas where gas and liquid flowed, respectively. The reactor was 192 mm × 97 mm (length × width). Experimental data were obtained for 2 M NaOH and 20 vol % CO2 inlet concentrations, for various liquid and gas flow rates, while keeping the molar flow rate ratio CO2/NaOH at 0.6. Results showed that in less than 1.2 s gas residence time approximately 30% of the carbon dioxide was removed. A two-dimensional model of the reactor where the solid area of the mesh was neglected and its percentage open area was used to modify the effective length of the reactor (segregated model) was formulated. This model's predictions gave better agreement with the experimental results compared to a pseudohomogeneous model where the diffusivities in the mesh were approximated with effective diffusivities based on mesh percentage open area. The model indicated that carbon dioxide was consumed within a short distance from the gas-liquid interface and the main mass transfer resistance was located in the mesh. Increasing the open area of the mesh increases CO2 removal as observed both theoretically and experimentally.
Keywords: Liquids; Absorption; Mass transfer; Membranes; Gases